The heterogeneous and transfer effects of a texting-based intervention on enhancing university English learners' vocabulary knowledge. Issue 1 (2nd January 2023) - Li, Jia; Ji, Linying; Deng, Qizhen
Abstract: Despite the growing body of technology-assisted vocabulary intervention studies, few have addressed learning outcomes beyond target vocabulary and the interaction between the interventions and English language learners' (ELLs) initially different levels of vocabulary knowledge. The study examined the differential effects of a texting-based intervention on ELLs' learning of target (direct effect) and general vocabulary knowledge (transfer effect) as a function of learners' initial vocabulary levels. Canadian undergraduate ELLs ( N = 115) participated in a 9-week intervention study. The findings showed that texting-based instruction effectively supported university ELLs' acquisition of academic vocabulary; varied direct and indirect learning outcomes were found given learners' different initial vocabulary levels. These results provide insights into the design of future vocabulary interventions by considering the complex interactions between learners' initial vocabulary knowledge and the technology scaffoldings used for interventions.